Implementation of Multiculturalism Values in Catholic Religious Education Lessons - Johannes Sohirimon Lumbanbatu; Din Oloan Sihotang; Ermina Waruwu; Elisa Br Ginting; Evani Simamora; Mariana Siregar; Sherly Yasinta Manalu (Journal of Innovation in Educational and Cultural Research, 2024)
Empathy and tolerance towards individuals with different beliefs and cultures is decreasing. This research conducted and analyzed the values of multiculturalism applied to Catholic religious education learning in schools. This research also aims to determine and measure the impact received after implementing the values of multiculturalism in learning Catholic religious education for students. The method used in this research was a qualitative approach with data collection techniques through observation, interviews, and documentation. The findings show that applying multiculturalism values in Catholic religious education learning can develop students’ understanding, skills, and attitudes in facing an increasingly multicultural world. Catholic Religious Education can positively contribute to peace and tolerance between religious communities. This can also positively contribute to world education and culture by helping increase readers' understanding of the importance of respecting religious and cultural differences.